Oral Submucous Fibrosis – An Ayurvedic Perspective - Aparna Sharma (New Advances in Medicine and Medical Science Vol. 6, 2023)
Oral Submucus Fibrosis (OSMF) is a pre-malignant condition for approximately 2% of the cases, leading to a significant deterioration in the Quality of Life, and nutrition. The symptoms of OSMF include pain, burning sensation, intolerance to spicy food, taste disorders, dry mouth, reduced opening of mouth, dysphagia, altered tone and decreased mobility of the tongue. Ayurveda refers to a few similar illnesses as Tridoshaj Mukhapaka and recommends several therapy modalities, including local therapies such as Gandusha and systemic ones such as consumption of Rasayana, Tridoshaghna herbs and herbals, as well as Nidana Parivarjana / abstinence from addictions. This chapter discusses many areas of OSMF as literary and clinical studies relevant to OSMF / Tridoshaj Mukhapaka in modern medicine, such as prevention, surgery, diet, lifestyle, physiotherapy, Ayurveda, and other Complementary Alternative Medicines. Ayurvedic preventive & curative protocols are detailed here.